2000
DOI: 10.1088/0266-5611/16/2/310
|View full text |Cite
|
Sign up to set email alerts
|

Integrable discretization of the modified KdV equation and applications

Abstract: An integrable discretization of the modified Korteweg-de Vries (mKdV) equation is considered. The mKdV algorithm is designed in terms of the resulting discrete mKdV equation. It is shown that a class of algebraic equations can be solved numerically in terms of the algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…In [13,14] the Bessel modification of measures appeared and a part of our main result which concerns (3) ⇒ (1) is proved. In a recent paper [15] the author deals with the Poisson structure and Lax pairs for the Ablowits-Ladik systems closely related to the Schur flows.…”
Section: We Can Modify the Second Statement By Observing Thatmentioning
confidence: 87%
See 1 more Smart Citation
“…In [13,14] the Bessel modification of measures appeared and a part of our main result which concerns (3) ⇒ (1) is proved. In a recent paper [15] the author deals with the Poisson structure and Lax pairs for the Ablowits-Ladik systems closely related to the Schur flows.…”
Section: We Can Modify the Second Statement By Observing Thatmentioning
confidence: 87%
“…x f. In [8] the authors deal with finite real Schur flows and suggest two more distinct Lax equations based on the Hessenberg matrix representation of the multiplication operator (see also [3]). In [13,14] the Bessel modification of measures appeared and a part of our main result which concerns (3) ⇒ (1) is proved. In a recent paper [15] the author deals with the Poisson structure and Lax pairs for the Ablowits-Ladik systems closely related to the Schur flows.…”
Section: Introductionmentioning
confidence: 87%
“…In the numerical simulation of the MKdV problem, we have found that the direct center-difference discretization does a poor job in adequately following the MKdV equation (and in conserving the corresponding integrals of motion). While one can also use the integrable scheme of Ablowitz-Ladik (see e.g., [2,18,19] and references therein), we have followed a different path here in spatially discretizing the partial differential equation and following the integrable discretization scheme of [20] for KdV and adapting it to the case of the MKdV. In particular, the spatially discrete version of our equation reads (with lattice spacing h):…”
Section: Numerical Methods and Evolution Of The Breather Latticementioning
confidence: 99%
“…The latter algorithm is formulated by discretizing the Schur flow which is an integrable system defined by a one-parameter deformation equation of the Szegö OPs. The discrete Schur flow has applications not only to a continued fraction expansion but also to a computation of zeros of polynomials [25]. The discrete Schur flow will see applications to various problems in applied science.…”
mentioning
confidence: 99%